PENGARUH MODEL PROJECT BASED LEARNING (PjBL) BERBANTUAN EDUCAPLAY TERHADAP HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR PADA SISWA KELAS III SDIT AL IMAM ASY-SYAFI’I NGAWI - Nadila Dyah Purnama Sari; Nofita Lestariningsih; Aulia Fajar Khasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This  study  addresses  the  low  mathematics  learning  outcomes  of  third-grade  students  on  plane  geometry  material  at  SDIT  Al  Imam  Asy-Syafi’i  Ngawi,  which  are  influenced  by  teacher-centered  learning  and  limited  use  of  interactive  media.  The  purpose  of  this  research  is  to  determine  the  effect  of  the  Project  Based  Learning  (PjBL)  model  assisted  by  Educaplay  on  students’  learning  outcomes.  This  study  employed  a  quantitative  approach  with  a  quasi-experimental  method  using  a  nonequivalent  control  group  design.  The  sample  consisted  of  40  students  divided  into  an  experimental  class  and  a  control  class.  Data  were  collected  through  multiple-choice  tests  administered  as  pretest  and  posttest.  The  data  analysis  techniques  included  validity  and  reliability  tests,  normality  and  homogeneity  tests,  as  well  as  hypothesis  testing  using  paired  sample  t-test  and  independent  sample  t-test.  The  results  showed  that  the  average  score  of  the  experimental  class  increased  significantly  from  pretest  to  posttest  compared  to  the  control  class.  This  indicates  that  the  application  of  the  PjBL  model  assisted  by  Educaplay  has  a  positive  and  significant  effect  on  students’  mathematics  learning  outcomes,  particularly  in  plane  geometry  material.  Therefore,  this  model  can  be  used  as  an  effective  and  innovative  learning  alternative  to  improve  student  engagement  and  achievement.